PENGUKURAN EFEKTIVITAS APLIKASI NOTA DAN SURAT PERINTAH JALAN DENGAN MENGGUNAKAN MICROSOFT EXCEL UNTUK MEMPERLANCAR DISTRIBUSI BARANG PADA MODERN RETAIL ROEMAH KITA GRESIK - Syech Tufail; Joni Dwi Pribadi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Note and road warrant is one of the most important things on a transaction media to improve service quality and expedite the distribution of goods. Based on research from Modern Retail Roemah Kita Gresik (Semen Indonesia Distributor), there are some problems about transaction media wich is note and road warrant still using manual/handwritten. From that problem, researcher have goals to give some solution wich is making transaction media note and road warrant digitals then printed, so it can improve the service quality and expedite the distribution of goods on Modern Retail Roemah Kita Gresik. This research is a type of action research, that are do something activities and solve the problem. Action research have some important element, wich is planning, action, observation, and reflection. Data collection methods used are interviews, observation, documentation, and questionnaires. The research was conducted with 12 respondents who had filled out a questionnaire using the SUS method, the distribution of the questionnaires in the study had very effective results and was feasible to use. The results of this study are proven by SUS with a grade A and a score of 85. This can be concluded that Modern Retail Roemah Kita Gresik can use note and warrant road digital as transaction media to improve service quality and epedite the distribution goods on the company.promotions, so as to stimulate purchasing interest in their products.